Ferroptosis: Mechanism and potential applications in cervical cancer - Chang, Xiangyu; Miao, Jinwei (Frontiers in Molecular Biosciences, 2023)
Ferroptosis is a distinct form of cell death mechanism different from the traditional ones. The main biochemical features of ferroptosis include lipid peroxidation, iron accumulation, and glutathione deficiency. It has already shown great potential in antitumor therapy. The progression of cervical cancer (CC) is closely associated with iron regulation and oxidative stress. Currently, existing studies have explored the role of ferroptosis in CC. Ferroptosis may provide a new research direction for treating CC. In this review, the factors and pathways, as well as the research basis of ferroptosis, which are closely related to CC, will be described. Furthermore, the review may provide potential future directions for CC research, and we believe that more studies concerning the therapeutic implications of ferroptosis in CC will come into notice in the future.